New method for reduction of harmonic of three phase rectifier using harmonic injection method - Mtair, Ali Saadon (2011)
The three-phase rectifier is becoming more common in power systems. This rectifier produces a non-linear waveform of the input current into a power system. This causes a number of problems for the power system control and for other electrical systems which require such rectifiers. In fact, the harmonic components generated by such power electronic devices have severe effects on several aspects of power networks especially on distribution. In addition, the high value of Total Harmonic Distortion (THD) causes undesirable distortion on the sinusoidal shape of the wave for the input current. This thesis proposes a new circuit for three-phase rectifier using harmonic current injection method. The proposed circuit was simulated using MATLAB software. A prototype of the proposed circuit has been developed. The proposed circuit uses active harmonic current injection method with a capacitor bank, which is simple compared to conventional circuits using harmonic current injection method with star-delta transformer as the current injection device. The prototype has been examined with feedback injection harmonic current to show the validity of the system. The comparison between simulation results and experimental results from the prototype shows minor difference. It has been observed that conventional three-phase rectifiers produce high THD for input currents, i.e., around 7.5%, while the proposed circuit has reduced the THD drawn from the input current supply down to 5.5%. This makes the waveform of the input current close to sinusoidal wave.